Distributed multicast address management in the global Internet. - Pejhan, S. (IEEE Journal on selected areas in communications)
We describe a distributed architecture for managing multicast addresses in the global Internet. A multicast address space partitioning scheme is proposed, based on the unicast host address and a per-host address management entity. By noting that port numbers are an integral part of end-to-end multicast addressing we present a single, unified solution to the two problems of dynamic multicast address management and port resolution. We then present a framework for the evaluation of multicast address management schemes, and use it to compare our design with three approaches, as well as a random allocation strategy. The criteria used for the evaluation are blocking probability and consistency, address acquisition delay, the load on address management entities, robustness against failures, and processing and communications overhead. With the distributed scheme the probability of blocking for address acquisition is reduced by several orders of magnitude, to insignificant levels, while consistency is maintained. At the same time, the address acquisition delay is reduced to a minimum by serving the request within the host itself. It is also shown that the scheme generates much less control traffic, is more robust against failures, and puts much less load on address management entities as compared with the other three schemes. The random allocation strategy is shown to be attractive primarily due to its simplicity, although it does have several drawbacks stemming from its lack of consistency (addresses may be allocated more than once)